CDO surfaces dynamics - Barbara Choros-Tomczyk; Wolfgang Karl Härdle; Ostap Okhrin (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2013)
Modelling the dynamics of credit derivatives is a challenging task in finance and economics. The recent crisis has shown that the standard market models fail to measure and forecast financial risks and their characteristics. This work studies risk of collateralized debt obligations (CDOs) by investigating the evolution of tranche spread surfaces and base correlation surfaces using a dynamic semiparametric factor model (DSFM). The DSFM offers a combination of flexible functional data analysis and dimension reduction methods, where the change in time is linear but the shape is nonparametric. The study provides an empirical analysis based on iTraxx Europe tranches and proposes an application to curve trading strategies. The DSFM allows us to describe the dynamics of all the tranches for all available maturities and series simultaneously which yields better understanding of the risk associated with trading CDOs and other structured products.
Keywords: C14; C51; G11; G17; 330; base correlation; collateralized debt obligation; curve trade; dynamic factor model; semiparametric model